Determinants of happiness among secondary school students in Iceland - Kristbjörg T. Haraldsdóttir 1976- (2015)
Happiness has recently received increased attention within the field of psychology. When exploring the determinants of happiness research has mainly focused on the happiness concerning adults. The aim of the present study is to investigate the determinants of happiness among secondary students in Iceland. Population dataset from the Icelandic Centre for Social Research and Analysis was used in the current study. A sample of 2070 Icelandic secondary school students aged 16 to 23 years was analyzed. The results show that the majority of Icelandic secondary school students describe themselves as happy. Perception of financial status at home, physical health, emotional support from parents, and emotional support from friends are strong predictors of Icelandic secondary school students’ happiness. The findings will hopefully give a better understanding about which factors are strong predictors of happiness. Many procedures were left out, therefore a more complex analysis needs to be carried out in order to get a better insight into which factors contribute to secondary school students’ happiness. Key words: happiness, students, physical health, emotional support, well-being Hamingja hefur á undanförnum árum fengið aukna athygli innan sálfræðinnar. Rannsóknir sem einblína á áhrifaþætti hamingju hafa þó aðallega einblínt á hamingju fullorðinna. Markmið þessarar rannsóknar er að athuga hvaða þættir hafa áhrif á hamingju íslenskra framhaldsskólanema. Notað var gagnasett frá Rannóknum og greiningu var í núverandi rannsókn. Úrtakið samanstóð af 2070 nemendum í framhaldsskólum á öllu landinu á aldrinum 16 til 23 ára. Niðurstöður sýndu að meirihluti íslenskra framhaldsskólanema telja sig vera hamingjusama. Fjárhagsleg staða fjölskyldu, líkamleg heilsa, tilfinningalegur stuðningur frá foreldrum og tilfinningalegur stuðningur frá vinum voru sterkustu forspárþættirnir fyrir hamingju framhaldsskólanema á Íslandi. Niðurstöðurnar munu vonandi varpa frekara ljósi á hvaða áhrifaþættir stuðla að hamingju unglinga og ungs fólks. ...